-6(3z-2)=5-4z

Simple and best practice solution for -6(3z-2)=5-4z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(3z-2)=5-4z equation:


Simplifying
-6(3z + -2) = 5 + -4z

Reorder the terms:
-6(-2 + 3z) = 5 + -4z
(-2 * -6 + 3z * -6) = 5 + -4z
(12 + -18z) = 5 + -4z

Solving
12 + -18z = 5 + -4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '4z' to each side of the equation.
12 + -18z + 4z = 5 + -4z + 4z

Combine like terms: -18z + 4z = -14z
12 + -14z = 5 + -4z + 4z

Combine like terms: -4z + 4z = 0
12 + -14z = 5 + 0
12 + -14z = 5

Add '-12' to each side of the equation.
12 + -12 + -14z = 5 + -12

Combine like terms: 12 + -12 = 0
0 + -14z = 5 + -12
-14z = 5 + -12

Combine like terms: 5 + -12 = -7
-14z = -7

Divide each side by '-14'.
z = 0.5

Simplifying
z = 0.5

See similar equations:

| -2x=-60 | | a=46 | | 3x+6=81 | | -2y-15=-5 | | -9(x-3)=-4(x+3)-2x | | 4=-2k+8 | | 148-7x=20x-19 | | -3x+5=-3x+10 | | 12x-8x=35-15x | | c=486+19n | | 2.2n+0.8+5=4n | | 160=10(n+10) | | 9-9x=39-30x | | -14=6z | | 14x-9+2x-5=13x-4+2x | | 1/2=x+3/8 | | 5y+2=1.2(10y+4) | | (6x+2)+(5x)=90 | | -153-9x=39-30x | | x-3=50 | | 71-3x=33x+23 | | x+6x+2x=180 | | -5(m-9)-4(-5m-8)=14(m+3)+6 | | 100=76+2x | | 35X+45X-3X+35-45+108=209 | | 6x+2=5(x-2)+8 | | X=4x-20 | | -32-2x=8+-7x | | g/2-19=-17 | | 8-3y=9-4y | | (2/2+5x)=0 | | 18-x+18(3x)+x=180 |

Equations solver categories